TANTANGAN GURU DI ERA GLOBALISASI DALAM MENANAMKAN NILAI KEJUJURAN TINJAUAN PRESPEKTIF ISLAM UNTUK ANAK - Makhmudah, Siti (Program Studi Manajemen Pendidikan Islam (MPI) STAI Nahdlatul Ulama (STAINU) Malang, 2024)
In this era of globalization, advances in technology and information are growing rapidly. The moral value of children is increasingly worrying along with the decline in the value of honesty. Many children violate their honesty in their pursuit of fame in this era of globalization. For example, a child lies asking for money from his parents to buy school supplies, but the money is bought an internet quota to play social media. Teachers are challenged to instill the value of honesty as early as possible in children, because Elementary School (SD/MI? is the initial foundation for the formation of children's character. This study aims to determine how teachers in the era of globalization instill the value of honesty in the Islamic perspective review in early childhood, and to find out the benefits of being honest. The research method uses qualitative data. From the results of research on the challenges of teachers in the era of globalization in instilling the value of honesty from an Islamic perspective in early childhood, it can be concluded that: (1) The way teachers instill the value of honesty in early childhood education is through storytelling, role playing. Teachers become role models for children in behaving and acting, avoiding lies, being open and it is better to be quiet than to lie. (2) the advantages of being honest are going to heaven, gaining the trust of others, having a calmer life, having lots of friends, getting great rewards and getting forgiveness from Allah.